Impact of Symbiosis Between Trichomonas vaginalis and Mycoplasma hominis on Vaginal Dysbiosis: A Mini Review - Margarita, Valentina; Fiori, Pier Luigi; Rappelli, Paola (Frontiers in Cellular and Infection Microbiology, 2020)
The protozoon Trichomonas vaginalis is responsible for trichomoniasis, a prevalent sexually transmitted infection associated with increased risk of HIV infection and adverse pregnancy outcomes. The protozoon has the surprising ability to establish a symbiotic relationships with other microorganisms. In fact, most T.vaginalis isolates host intracellularly the vaginal bacterium Mycoplasma hominis, and can harbor up to four dsRNA viruses. Moreover, recently a novel Mycoplasma species, named Ca. Mycoplasma girerdii, has been described in association with trichomonad cells. T.vaginalis colonizes the human vagina and its presence causes profound alterations of the resident microbiota, leading to dysbiosis. In healthy women vaginal microbiota is characterized by the presence of a complex population of aerobic and anaerobic microorganisms, living in a physiologically dynamic system dominated by bacteria of the genera Lactobacillus. The most common microbial vaginal imbalance is bacterial vaginosis, a polymicrobial disease associated with several adverse reproductive outcomes and increased risk of HIV infection. Here, we review the current knowledge regarding the interactions between both T.vaginalis and M.hominis and the vaginal microbiota, and we discuss the possibility of a cooperation between T.vaginalis and its symbionts in the development of vaginal dysbiosis.